THE INFLUENCE OF REDUCING RATES AND METHODS OF TAX CALCULATION ON TAXPAYERS COMPLIANCE OF SMALL AND MEDIUM MICRO BUSINESS: EXPERIMENTAL STUDY IN YOGYAKARTA - Wulan, Dewi Nawang; Kresnawati, Etik (Riset Akuntansi dan Keuangan Indonesia, 2019)
This study investigates whether the issuance of Government Regulation No. 23/2018 regarding the reduction of Micro, Small and Medium Enterprises (MSME) tax rates and changes in reporting methods will affect the preferences of MSME taxpayer compliance. Study were carried out on MSME actors in Yogyakarta using laboratory experimental methods. The test results show that the reduction in tax rates increases the preference for MSME taxpayer compliance. When given the choice to determine the method to be used in calculating taxes, 50% of participants choose to use the final tax rate and the remainder use the normal tax rate method. The option chosen is not based on the complexity of the method but because of the sense of fairer they feel. The last, participants does not refuse when required to use tax calculation using the normal tax rate method after seven years. The test results indicate that the issuance of Government Regulation No. 23/2018 will be able to increase MSME taxpayer compliance in the future.This study investigates whether the issuance of Government Regulation No. 23/2018 regarding the reduction of Micro, Small and Medium Enterprises (MSME) tax rates and changes in reporting methods will affect the preferences of MSME taxpayer compliance. Study were carried out on MSME actors in Yogyakarta using laboratory experimental methods. The test results show that the reduction in tax rates increases the preference for MSME taxpayer compliance. When given the choice to determine the method to be used in calculating taxes, 50% of participants choose to use the final tax rate and the remainder use the normal tax rate method. The option chosen is not based on the complexity of the method but because of the sense of fairer they feel. The last, participants does not refuse when required to use tax calculation using the normal tax rate method after seven years. The test results indicate that the issuance of Government Regulation No. 23/2018 will be able to increase MSME taxpayer compliance in the future.